Turbin angin poros vertikal tipe Savonius bertingkat dengan variasi posisi sudut - Alit, I.B.; Nurchayati, Nurchayati; Pamuji, S.H. (Universitas Mataram, 2016)
Wind turbine is a technology that converts wind energy to electric power. A Savonius type rotor blade is a simple wind turbine that operates on the concept of drag. The turbine has a potential to be developed as it has a simple construction and it is suitable for low wind speeds. Savonius rotor can be designed with two or three blades in single level or multi-levels. This research was conducted to obtain two levels wind turbine performance characteristics with variations in wind speed and different positions of angle on each level. The variations of the angle position of the wind turbine were 0°, 30°, 45°, 60°, and 90° in each stage. The result shows that the performance of the wind turbine is inversely to the degree of the angle position. The maximum rotation speed of the rotor was about 150.6 rpm that was generated at the wind speed of 5 m/s and the angle position of 0°.